2020
DOI: 10.21278/brod71105
|View full text |Cite
|
Sign up to set email alerts
|

A Numerical Study on the Open Water Performance of a Propeller With Sinusoidal Pitch Motion

Abstract: When a ship operates in waves, the ship moves with 6 degrees-of-freedom, and a propeller at the stern of the ship cannot avoid moving due to the ship motion. Therefore, it is important to analyse the propulsion performance while considering the ship motion in waves for efficient ship operation. The pitch motion of the ship has a dominant effect on the variation of the propeller performance and results in sinusoidal pitch motion of the propeller. In this study, a numerical analysis was done using a KP458 model … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…During our pre-study, it was found that the wake flow characteristics of the ducted propellers calculated in a cylindrical outer domain were the same as those obtained from a rectangular one. Therefore, a rectangular outer fluid domain was adopted, which is same as those in Dubas et al (2015), Hu et al (2019) and Jang et al (2020). Diameter of the rotating domain is 1.0 D .…”
Section: Numerical Settingsmentioning
confidence: 99%
“…During our pre-study, it was found that the wake flow characteristics of the ducted propellers calculated in a cylindrical outer domain were the same as those obtained from a rectangular one. Therefore, a rectangular outer fluid domain was adopted, which is same as those in Dubas et al (2015), Hu et al (2019) and Jang et al (2020). Diameter of the rotating domain is 1.0 D .…”
Section: Numerical Settingsmentioning
confidence: 99%
“…Gaggero and Villa (2018) proposed cavitating propeller performance with inclined shaft conditions with OpenFOAM (PPTC 2015 Test Case). Paik et al (2020) studied open water propeller performance with sinusoidal pitch motion, which was set at inclined angles (−10° to 10°) by STAR-CCM+ software. An optimization procedure for propeller selection for different shaft inclinations has been conducted by Soares et al (2022).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, the most common parameters applied to define the propeller behaviors are propeller rotation, propeller diameter and vessel velocity. In recent years, the effects of the parameters on the propeller have been investigated due to highspeed and maneuvering capability needs [1][2][3][4].…”
Section: Introductionmentioning
confidence: 99%